The effect of electron beam irradiation on the tensile properties of pineapple leaf fibre (PALF) reinforced high impact polystyrene (HIPS) composites - Siregar, Januar Parlaungan; Salit, Mohd Sapuan; Abdul Rahman, Mohd Zaki; Mohd Dahlan, Khairul Zaman (2009)
The effects electron beam of irradiation on tensile properties of pineapple leaf fibre reinforced high impact polystyrene (HIPS) composites was studied. Two types of crosslinking agent that has been used in this study were trimethylolpropane triacrylate (TMPTA) and tripropylene gylcol diacrylate (TPGDA). A 50 wt.% of PALF was blended with HIPS and crosslinking agent using Brabender melt mixer at 165°C. The composites were then irradiated using a 3 MeV electron beam accelerator with dosage of 0-100 kGy. The tensile strength and tensile modulus of composites were measured and the effects of crosslinking agent were also compared.